2004
DOI: 10.1182/blood-2004-02-0408
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-dose melphalan improves survival of myeloma patients aged 50 to 70: results of a randomized controlled trial

Abstract: High-dose therapy is an effective standard treatment for multiple myeloma patients. Evidence that intermediate-dose therapy improves survival is limited. At diagnosis, about 70% of patients are older than 65. Intermediate-dose regimen is very well tolerated in older patients. In a multicenter study, 194 patients were randomized to receive at diagnosis either conventional chemotherapy (6 courses of oral melphalan and prednisone [MP]) or intermediate-dose therapy (2 courses of melphalan at 100 mg/m 2 [MEL100]) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
190
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(200 citation statements)
references
References 20 publications
(20 reference statements)
3
190
1
6
Order By: Relevance
“…Intensified chemotherapy with ASCT has been found to be superior to conventional therapy in the treatment of both younger and elder patients with MM, [19][20][21] and ASCT has become the standard therapy for newly diagnosed MM patients. In general practice, almost all patients with MM less than 65 years old undergo ASCT after initial chemotherapy such as VAD.…”
Section: Discussionmentioning
confidence: 99%
“…Intensified chemotherapy with ASCT has been found to be superior to conventional therapy in the treatment of both younger and elder patients with MM, [19][20][21] and ASCT has become the standard therapy for newly diagnosed MM patients. In general practice, almost all patients with MM less than 65 years old undergo ASCT after initial chemotherapy such as VAD.…”
Section: Discussionmentioning
confidence: 99%
“…29 High dose chemotherapy with AHSCT has become a standard treatment for younger and fit MM patients, as it is capable of providing sustained remission with improvement in both event-free survival [1][2][3]30 and overall survival. 1,2,30 The alkylating agent melphalan, a mainstay of MM therapy, has been shown to hamper stem cell collection and is avoided in the initial management of transplant-eligible patients. [31][32][33] Therefore, any novel agents used in the treatment of MM in transplant-eligible patients must likewise be evaluated for possible deleterious effects on HSC mobilization and collection.…”
Section: Discussionmentioning
confidence: 99%
“…The latter was included in part because of data showing that this reduced-intensity approach, with melphalan at 100 mg/m 2 (Mel 100), showed a survival advantage compared to MP in myeloma patients aged 50-70 years. 33 In the final analysis of this three-arm study, MPT was associated with a higher risk of grade 3 or 4 neutropenia, infections, thrombocytopenia, thromboem- treatment overall in the MPT cohort. As was the case in the Italian study of MPT, the IFM trial found a higher overall response rate for MPT compared with MP (Table 8), and a better response quality as well, with more CRs and very good partial responses.…”
Section: Mp + Thalidomidementioning
confidence: 99%